2013
DOI: 10.1038/srep03484
|View full text |Cite
|
Sign up to set email alerts
|

Infrared laser pulse triggers increased singlet oxygen production in tumour cells

Abstract: Photodynamic therapy (PDT) is a technique developed to treat the ever-increasing global incidence of cancer. This technique utilises singlet oxygen (1O2) generation via a laser excited photosensitiser (PS) to kill cancer cells. However, prolonged sensitivity to intensive light (6–8 weeks for lung cancer), relatively low tissue penetration by activating light (630 nm up to 4 mm), and the cost of PS administration can limit progressive PDT applications. The development of quantum-dot laser diodes emitting in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 46 publications
2
79
0
8
Order By: Relevance
“…The complex intracellular antioxidant system that degrades H 2 O 2 was described phenomenologicaly in the model (Sokolovski et al, 2013) through the redox-balancing cascade reactions corresponding to key antioxidant enzymes, i.e. the thioredoxin peroxidase/thioredoxin/thioredoxin reductase (Tpx/Trx/TR) and glutathione peroxidase/glutathione/glutathione reductase (Gpx/GSS/GR) systems (see module 9 in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The complex intracellular antioxidant system that degrades H 2 O 2 was described phenomenologicaly in the model (Sokolovski et al, 2013) through the redox-balancing cascade reactions corresponding to key antioxidant enzymes, i.e. the thioredoxin peroxidase/thioredoxin/thioredoxin reductase (Tpx/Trx/TR) and glutathione peroxidase/glutathione/glutathione reductase (Gpx/GSS/GR) systems (see module 9 in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was shown by this group that if one uses narrow laser beams (of about 0.1 mm) and reaches very high density of laser power (~200 W/cm 2 ), direct oxygen excitation by IR laser radiation causes photodamage of cancer cells with the maximum of the action spectrum at 1273 nm [22]. Even stronger effect was reported when narrow laser beams and nanosecond laser pulses were used together [24].…”
Section: Figmentioning
confidence: 96%
“…However, the maximum energy of a laser peak (~20 MW/cm 2 ) used in our work was insufficient for saturation of the electronic transition in oxygen molecules, for which ~10 6 higher energy is required. The peak energy is also 200 times smaller than that used in experiments by Sokolovsky et al who suggested strong increase of singlet oxygen reactivity under pulsed laser generation [24].…”
Section: Carbon Tetrachloridementioning
confidence: 96%
See 2 more Smart Citations